Batik Jambi: A Hidden Gem in the Heart of Sumatra - Nandya, Putri Oktarin; Anggita, Marissa; Nalendra, R Bagas Jalu; Agustin, Niken Ayu Putri; Jamil, Muhammad Safwan; Mualif, Syamsul; Prastiwi, Juliyani; Resik, Kemas Muhammad Sultan (Jurnal Prajaiswara, 2025)
Introduction/Main Objectives: This study examines Jambi batik as a cultural heritage that has historical, symbolic, and economic value for the Jambi community. The research focuses on the history and development of Jambi batik as a cultural identity, the philosophical meaning and symbolism of its motifs, and its role as a creative economy product. Research Methods: This study uses a qualitative approach with a descriptive-analytical research type through literature studies, observations, and interviews. Using C.S. Peirce's Semiotic framework for motif analysis, this study found that the existence of Jambi Batik is the result of a long process of interaction between Malay, Javanese, Arabic, and Chinese cultures. Finding/Results: Jambi Batik motifs such as Angso Duo, Kapal Sanggat, and Durian Pecah contain deep symbolism that reflects the value of local wisdom. These motifs not only function as aesthetic elements but are also classified as conventionally agreed-upon symbols. In addition, the results of the study indicate that Jambi Batik plays a significant role as a creative economy commodity. Batik production makes a real contribution to community economic empowerment, particularly through job creation, MSME development, and market expansion through innovation and cultural storytelling. Conclusion: Overall, this research confirms that Jambi batik is a "cultural gem" that serves not only as a symbol of regional identity but also as a strategic economic asset. Preservation through design innovation, improved production quality, education for the younger generation, and cross-stakeholder collaboration are key to ensuring the sustainability of Jambi batik.